2011
DOI: 10.1130/l118.1
|View full text |Cite
|
Sign up to set email alerts
|

Paleoseismologic evidence for the relatively regular recurrence of infrequent, large-magnitude earthquakes on the eastern North Anatolian fault at Yaylabeli, Turkey

Abstract: Paleoseismologic trenches excavated across the eastern part of the North Anatolian fault at Yaylabeli, Turkey, provide evidence for fi ve surface ruptures during the past 2000 yr. We interpret these events as: (1) the historical 1939 M w 7.9 earthquake; (2) the historical 1254 A.D. earthquake; (3) the historical 1045 A.D. earthquake; (4) an earthquake that occurred between 660 A.D. and 1020 A.D., most probably between 717 A.D. and 844 A.D.; and (5) an earthquake that occurred between 302 A.D. and 724 A.D., pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
6
32
0
1
Order By: Relevance
“…The peak at 1430 AD that is represented by two carbonate samples with more precise relative age errors corresponds to the most prominent event peak obtained from the carbonate dating (Figure S8 and Table ). This peak is consistent, within the range of analytical error, with the results of all paleoseismic trenching studies conducted to the east of Reşadiye (Fraser et al, ; Hartleb et al, ; Kozacı et al, ; Zabcı et al, ). The event dated in these trenches was attributed to the 1254 AD earthquake in the historical earthquake records.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The peak at 1430 AD that is represented by two carbonate samples with more precise relative age errors corresponds to the most prominent event peak obtained from the carbonate dating (Figure S8 and Table ). This peak is consistent, within the range of analytical error, with the results of all paleoseismic trenching studies conducted to the east of Reşadiye (Fraser et al, ; Hartleb et al, ; Kozacı et al, ; Zabcı et al, ). The event dated in these trenches was attributed to the 1254 AD earthquake in the historical earthquake records.…”
Section: Discussionsupporting
confidence: 87%
“…Note that horizontal lines extended to the related peak on relative probability curve project our results. T1 = Fraser (), T2 = Zabcı et al (), T3 = Polat et al (), T5 = Fraser et al (), T6 = Kozacı et al (), T7 = Hartleb et al ().…”
Section: Coseismic Fluid Circulation On Active Fault Zonesmentioning
confidence: 92%
See 2 more Smart Citations
“…When we considered these earthquakes' locations, formation timings and magnitudes, it seems that the large earthquakes, which eventuated on the EFZ and were quite close to the YGFZ, triggered each other. The palaeoseismological studies carried out in the northern branch of the NAFZ suggested that the estimated recurrence interval is 150-300 years for surfaceruptured large earthquakes (Hartleb, Dolan, Kozaci, Akyuz, & Seitz, 2006;Ikeda et al, 1991;Kozacı, Dolan, & Finkel, 2009;Kozacı, Dolan, Yönlü, & Hartleb, 2011;Özaksoy et al, 2010;Rockwell, Barka, Dawson, Akyuz, & Thorup, 2001;Rockwell et al, 2009), while palaeoseismological studies on the southern branch are very limited, except for Yoshioka and Kuşçu (1994), Kürçer et al (2008), Belindir (2008) and Özalp et al (2013); however, Özalp et al (2013) reported that the return period of the greater earthquakes that occurred on the southern branch was not regular, but these fault segments have the potential to produce earthquakes on the northern branch. Additionally, Belindir (2008) reported an earthquake recurrence interval on the YGFZ that ranged between 253 and 925 years.…”
Section: Interpretation Of Palaeoseismological and Geoarchaeological mentioning
confidence: 99%